Nanotherapeutics for Alzheimer's Disease with Preclinical Evaluation and Clinical Trials: Challenges, Promises and Limitations - Bukhari, Syed N. A. (Current Drug Delivery, 2022)
Alzheimer’s Disease (AD), a progressive and irreversible neurodegenerative disorder, is the most common form of dementia worldwide. Currently, there is no disease-modifying AD drug, and the development of effective treatments is made even harder by the highly selective nature of the Blood-Brain Barrier (BBB) that allows the passage only of molecules with specific chemicalphysical properties. In this context, nanomedicine and its Nanoparticles (NPs) offer potential solutions to the challenge of AD therapy, in particular, the requirements for i) BBB crossing, ii) multitarget therapy iii) enhancement of pharmacokinetics; and iv) more precise delivery. In addition, the possibility to optimize NP biophysical and biological (i.e. target-specific ligands) properties allows for highly tailored delivery platforms. Preclinical studies have demonstrated that nanotherapeutics provide superior pharmacokinetics and brain uptake than free drugs and, on the other hand, these are also able to mitigate the side-effects of the symptomatic treatments approved by the FDA. Among the plethora of potential AD nanodrugs, multitarget nanotherapeutics are considered the most promising strategy due to their ability to hit simultaneously multiple pathogenic factors, while nano-nutraceuticals are emerging as interesting tools in the treatment/prevention of AD. This review provides a comprehensive overview of nanomedicine in AD therapy, focusing on key optimization of NPs properties, most promising nanotherapeutics in preclinical studies and difficulties that are limiting the efficient translation from bench to bedside.
Keywords: Alzheimer’s Disease